2011
DOI: 10.1073/pnas.1013391108
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation kinetics and phase of laboratory and ambient secondary organic aerosol

Abstract: Field measurements of secondary organic aerosol (SOA) find significantly higher mass loads than predicted by models, sparking intense effort focused on finding additional SOA sources but leaving the fundamental assumptions used by models unchallenged. Current air-quality models use absorptive partitioning theory assuming SOA particles are liquid droplets, forming instantaneous reversible equilibrium with gas phase. Further, they ignore the effects of adsorption of spectator organic species during SOA formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

54
641
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 383 publications
(703 citation statements)
references
References 36 publications
54
641
8
Order By: Relevance
“…The mass loss for AIDA experiments (Fig. 2B) was because of semivolatile vapor loss, consistent with other isothermal observations (14,38). At PSI and CMU, however, particle diameters were stable after SOA formation, and mass losses were associated with particle number loss via deposition to the walls.…”
Section: Resultssupporting
confidence: 75%
“…The mass loss for AIDA experiments (Fig. 2B) was because of semivolatile vapor loss, consistent with other isothermal observations (14,38). At PSI and CMU, however, particle diameters were stable after SOA formation, and mass losses were associated with particle number loss via deposition to the walls.…”
Section: Resultssupporting
confidence: 75%
“…Our study suggests that this mechanistic interaction between climate-relevant OA and healthrelevant PAHs should be explicitly represented in PAH chemical transport models. We show that the OA coating is likely more effective in shielding PAHs in the middle/high latitudes compared with the tropics because of differences in OA properties [semisolid when cool/dry (42)(43)(44) vs. liquid-like when warm/humid, as shown by OA measurements (27,28)]. Thus, the effectiveness of shielding depends on the viscosity of OA that varies with temperature, RH, and the atmospheric aging of complex OA coatings.…”
Section: Discussionmentioning
confidence: 99%
“…We report here an expanded investigation of the ozonolysis of trans-3-hexene in which particle composition is probed as a function of size. In addition, the influence of water vapor, OH and SCI scavengers, as well as the phase state of SOA particles (which plays critical roles in various physical and chemical processes of aerosols) [47][48][49][50][51][52][53][54][55][56] are elucidated and possible mechanisms are examined in light of predictions of a box model for this system. Initial studies of the ozonolysis of the much larger and complex biogenic alkene a-cedrene are also reported, and it is shown that the mechanism of particle formation for this sesquiterpene is different from that for trans-3-hexene.…”
Section: Introductionmentioning
confidence: 99%